Serum GFAP, NfL, and tau concentrations are associated with worse neurobehavioral functioning following mild, moderate, and severe TBI: a cross-sectional multiple-cohort study - Edwards, Katie A.; Lange, Rael T.; Lippa, Sara M.; Brickell, Tracey A.; Gill, Jessica M.; French, Louis M. (Frontiers in Neurology, 2024)
Introduction The purpose of this study was to examine whether blood-based biomarkers associate with neurobehavioral functioning at three time points following traumatic brain injury (TBI). Materials and methods Participants were 328 United States service members and veterans (SMVs) prospectively enrolled in the Defense and Veterans Brain Injury Center-Traumatic Brain Injury Center of Excellence (DVBIC-TBICoE) 15-Year Longitudinal TBI Study, recruited into three groups: uncomplicated mild TBI (MTBI, n = 155); complicated mild, moderate, severe TBI combined (STBI, n = 97); non-injured controls (NIC, n = 76). Participants were further divided into three cohorts based on time since injury (≤12 months, 3–5 years, and 8–10 years). Participants completed the Minnesota Multiphasic Personality Inventory-2-Restructured Format (MMPI-2-RF) and underwent blood draw to measure serum concentrations of glial fibrillary acidic protein (GFAP), neurofilament light (NfL), and tau. A total of 11 MMPI-2-RF scales were examined (e.g., depression, anxiety, anger, somatic, cognitive symptoms). Stepwise hierarchical regression models were conducted within each group. Results Significant associations were found between biomarkers and MMPI-2-RF scales (all p < 0.05; R2Δ > 0.10). GFAP was inversely related to (a) neurological complaints in the MTBI group at ≤12 months, (b) demoralization, anger proneness in the STBI group at ≤12 months, and (c) head pain complaints in the STBI group at 8–10 years. NfL was (a) related to low positive emotions in the NIC group; and inversely related to (b) demoralization, somatic complaints, neurological complaints, cognitive complaints in the MTBI group at ≤12 months, (c) demoralization in the STBI group at ≤12 months, and (d) demoralization, head pain complaints, stress/worry in the STBI group at 3–5 years. In the STBI group, there were meaningful findings (R2Δ > 0.10) for tau, NFL, and GFAP that did not reach statistical significance. Discussion Results indicate worse scores on some MMPI-2-RF scales (e.g., depression, stress/worry, neurological and head pain complaints) were associated with lower concentrations of serum GFAP, NfL, and tau in the sub-acute and chronic phase of the recovery trajectory up to 5 years post-injury, with a reverse trend observed at 8–10 years. Longitudinal studies are needed to help elucidate any patterns of association between blood-based biomarkers and neurobehavioral outcome over the recovery trajectory following TBI.